Strategi Pemasaran dan Prosedur Produksi Pakaian di Masa Pemulihan Pandemi Covid-19 pada Toko Lenka - Khoirunnisa, Hilda; Hamdan Ali Masduqie, Muhammad; Niti Purbayudha, Manida (Institut Agama Islam YPBWI Surabaya, 2024)
During the Covid-19 pandemic, many MSMEs had to close down due to the impact of economic instability. The sector that was also affected was the clothing trade. This happens because clothing is no longer the main priority for most people during Covid-19. As a result, clothing MSMEs have to rack their brains to keep their businesses running and survive amidst the lack of clothing enthusiasts. The aim of this research is to explain what and how the strategies and procedures were carried out at the Lenka store during the pandemic and during the recovery period from the Covid-19 pandemic. This research uses a qualitative approach with data collection techniques through natural observation and interviews. The results of this research show that there have been changes in strategy and procedures carried out at the Lenka store by prioritizing online sales on various social media. Apart from that, many ordering processes are also carried out using the Purchase Order (PO) system. Lenka is also developing her business by accepting orders for clothing MSMEs who are just starting out and don't yet have their own tailors so that they can realize their dream of having their own clothing business.